Early careers in education : perspectives for students and NQTs - Gillespie, Aidan (Emerald points., 2021)
Responding to a gap in the literature, this is the first book to bridge the divide between completing a professional course in education and entering into a practical career in education provision. Drawing on a variety of contributors including academics and Newly Qualified Teachers, this edited collection draws attention to new initiatives in particular areas of education, and provides reflection points for those entering in to a variety of careers in education. Consisting of short and concise chapters, the book encourages readers to examine their own perspectives on the content, consider the relevance of the issues presented, and even respond to these questions drawing on their own emerging expertise. Creating a space for readers to contextualise the issues raised in the dynamic contexts in which individual early career educators practice in, the authors equip readers to apply the contents to their own professional pathway. Presented thematically, and allowing for analysis of specific issues as well as overarching themes, this book is must-have reading for those who have just commenced a career in education or are just about to. Due to its boundary bridging focus, the book is of specific interest to final year students on education courses as well as those who have embarked on a career in teaching, or related fields.